Biomass Torrefaction Process, Product Properties, Reactor Types, and Moving Bed Reactor Design Concepts - Tumuluru, Jaya Shankar; Ghiasi, Bahman; Soelberg, Nick R.; Sokhansanj, Shahab (Frontiers in Energy Research, 2021)
Torrefaction, a thermal pretreatment process, is gaining attention as it improves biomass physical properties and chemical composition for recycling. During torrefaction, biomass is heated slowly in an inert environment to a maximum temperature of 300°C. The torrefaction process creates a solid uniform product with lower moisture and higher energy content than raw biomass. During torrefaction, moisture and some volatile organic compounds (VOCs) volatilize from the biomass. Depending on stoichiometry and other conditions, non-condensable gas species, including CO and CO2, are formed. Among the various torrefaction reactor designs, the moving bed reactor has gained attention as it is easy to operate and scale and helps produce a uniform torrefied product. However, there is a lack of literature on the torrefaction reactor design aspects and relevant design equations for estimating the dimensions of the torrefier based on its throughput. This article includes: (a) the impact of torrefaction on the product quality in terms of biomass physical properties and chemical composition; and (b) a model for designing a moving bed torrefier, considering fundamental heat and mass transfer calculations. This model includes a set of equations for basic calculations to configure the torrefaction reactor dimensions such as diameter and height of the moving bed torrefier for different capacities, based on target and calculated solids and gas velocities, residence times, and temperatures. The article also briefly describes the solid feed system, gas supply and recycle system, solid product management, torrefier gas monitoring, control system, and fugitive dust emissions control. Different moving bed torrefaction and gas recycle concepts are conceptualized to assess the features, advantages, and disadvantages of various design and operating concepts. These designs include example concepts for (a) vertical and horizontal torrefaction reactors; (b) torrefier gas recycle and oxidation of all or a portion of the torrefier off-gas; (c) counter and co-flowing gas and biomass in the torrefier; (d) controls for system temperatures, pressures, flow rates, and gas compositions; and (e) ability to sample the biomass feed, torrefied product, and gas streams for analysis as needed to investigate the thermal decomposition, physical behavior, and operational performance of the torrefaction system.